KISRUH PILKADA KABUPATEN PONOROGO: (Analisis Wacana Kritis Model Norman Fairclough tentang Pemberitaan Gugatan Pilkada Kabupaten Ponorogo pada Tanggal 22 Desember 2015- 21 Januari 2016) - Ayub Dwi Anggoro; Yusuf Adam Hilman (Jurnal Riset Komunikasi (JURKOM), 2018)
Research is called chaos election district ponorogo (discourse critical analysis model Norman Fairclough about news a lawsuit this election district Ponorogo on may 22 December 2015 - 21 January 2016). Methods used in research is descriptive method the critical analysis discourse model three dimensions “norman fairclough” .The purpose of this research isto review the news textThe result showed that the language of: diction, the use of the word, and selection in the source directly used in research, put the institution the constitutional court in the representation of negative. It is connected to ideology nationalism adopted by institutions the online media more defend sugiri. Nevertheless, representation besides pertaining to ideology adopted, also has connection with political interests from the media is the founder of institutions, in imaging positive on his party.